2004
DOI: 10.1002/em.20072
|View full text |Cite
|
Sign up to set email alerts
|

Examination of the potential genotoxicity of pure capsaicin in bacterial mutation, chromosome aberration, and rodent micronucleus tests

Abstract: There is widespread dietary exposure to capsaicin in the form of chili peppers, while capsaicin's analgesic qualities have led to increased use of a topical herbal remedy in various impure forms. Most recently, injection of pure capsaicin has been proposed as a means of relieving a variety of debilitating diseases, in which case tissues would receive relatively high and direct exposure. The purpose of the present study, where a series of standard assays were performed in accordance with the Organisation for Ec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 31 publications
3
17
0
Order By: Relevance
“…Taken together with the two rigorously conducted genotoxicity panels using pure capsaicin (Chanda et al 2004;Proudlock, Thompson, and Longstaff 2004), this naturally occurring molecule-which is present in many food, self-defense, and medical products-displays a very low carcinogenic potential.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Taken together with the two rigorously conducted genotoxicity panels using pure capsaicin (Chanda et al 2004;Proudlock, Thompson, and Longstaff 2004), this naturally occurring molecule-which is present in many food, self-defense, and medical products-displays a very low carcinogenic potential.…”
Section: Discussionmentioning
confidence: 99%
“…Genotoxic in both studies Richeux et al (1999) In vitro micronucleus and sister chromatid exchange in human peripheral blood lymphocytes Genotoxic in both studies Marques et al (2002) Bacterial mutation (S. typhimurium TA1535, TA1537, TA98, TA100 and E. coli WP2 uvrA), chromosomal aberration in human peripheral blood, and in vivo rat micronucleus Nongenotoxic in all studies Proudlock, Thompson, and Longstaff (2004) Bacterial mutation (S. typhimurium TA1535, TA1537, TA98, TA100 and E. coli WP2 uvrA), mouse lymphoma cell mutation, chromosomal aberration in human peripheral blood lymphocytes, and in vivo mouse micronucleus Genotoxic in bacterial mutation, chromosomal aberration and in vivo mouse micronucleus; weakly genotoxic in mouse lymphoma after metabolic activation a Based on an application area of approximately 4 cm 2 on the back of a mouse. Dose volume was 0.1 ml.…”
Section: Capsaicinmentioning
confidence: 98%
“…In a battery of studies, Chanda et al (2004) found that pure capsaicin induced a weak response after 4 h of treatment in the range of toxic concentrations in the mouse lymphoma assay but was non-mutagenic when treatment was extended to 24 h, and they commented that the criteria for positive results from this assay remain controversial. Results were uniformly negative using pure capsaicin in the Ames test and in human lymphocytes assayed for chromosomal aberrations (Chanda et al, 2004;Proudlock et al, 2004). Finally, in whole animal studies, bone marrow micronuclei were not induced either in the mouse (Chanda et al, 2004) or in the rat (Proudlock et al, 2004).…”
Section: Genotoxicitymentioning
confidence: 88%
“…Results were uniformly negative using pure capsaicin in the Ames test and in human lymphocytes assayed for chromosomal aberrations (Chanda et al, 2004;Proudlock et al, 2004). Finally, in whole animal studies, bone marrow micronuclei were not induced either in the mouse (Chanda et al, 2004) or in the rat (Proudlock et al, 2004).…”
Section: Genotoxicitymentioning
confidence: 88%
“…However other investigators using purer material in tests for chromosomal aberration, bacterial mutation, and the rodent micronucleus test did not confirm the genotoxicity of capsaicin. Genotoxicity was not established when material of 98.7% purity was used (78), whereas in another study, 99% pure capsaicin afforded only weak positive results (79), leading to the suggestion that impurities in the capsaicin material under test may have been a critical factor in the earlier experiments in which it was found to be genotoxic (77). Rodent studies (80) and epidemiology tentatively suggest that capsaicin may be carcinogenic (81)(82)(83)(84).…”
Section: Specific Toxicitiesmentioning
confidence: 92%